2016
DOI: 10.1186/s12889-016-3243-2
|View full text |Cite|
|
Sign up to set email alerts
|

Scaling-up an efficacious school-based physical activity intervention: Study protocol for the ‘Internet-based Professional Learning to help teachers support Activity in Youth’ (iPLAY) cluster randomized controlled trial and scale-up implementation evaluation

Abstract: BackgroundDespite the health benefits of regular physical activity, most children are insufficiently active. Schools are ideally placed to promote physical activity; however, many do not provide children with sufficient in-school activity or ensure they have the skills and motivation to be active beyond the school setting. The aim of this project is to modify, scale up and evaluate the effectiveness of an intervention previously shown to be efficacious in improving children’s physical activity, fundamental mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 60 publications
0
37
0
4
Order By: Relevance
“…This result supports findings by Jones et al [15], which showed that after training, educators self-efficacy around supporting children's FMS improved in the intervention group compared with the control group. Moreover, in school teachers there is evidence that professional development programs that improve teachers self-efficacy to provide physical education for children has a positive impact on children's physical activity [27]. Bandura defines self-efficacy as a person's beliefs about their ability to produce designated levels of performance for a certain task [28].…”
Section: Discussionmentioning
confidence: 99%
“…This result supports findings by Jones et al [15], which showed that after training, educators self-efficacy around supporting children's FMS improved in the intervention group compared with the control group. Moreover, in school teachers there is evidence that professional development programs that improve teachers self-efficacy to provide physical education for children has a positive impact on children's physical activity [27]. Bandura defines self-efficacy as a person's beliefs about their ability to produce designated levels of performance for a certain task [28].…”
Section: Discussionmentioning
confidence: 99%
“…As discussed previously, there is potential to reduce the burden of data collection by moving from objective data to subjective data. Additionally, there are recent examples of scaled up interventions successfully moving from face to face delivery to virtual delivery [38,39,44,45]. For example, due to significant costs, unaffordable in the real world, Goode and colleagues transformed an effective multi-component intervention targeting sedentary office workers (BeUpStanding TM program) into a web based scalable program that could be implemented directly by the workplaces [45].…”
Section: Barriersmentioning
confidence: 99%
“…Our efficacy study showed the SCORES intervention had positive effects on students’ physical activity levels, cardiorespiratory fitness and fundamental movement skills [ 51 ]. We are currently testing the effectiveness of a scalable version of the SCORES intervention, called iPLAY (internet-based Professional Learning to help teachers promote Physical activity in Youth) [ 53 ]. The SAAFE principles have also since evolved to support the delivery of school-based physical activity interventions targeting adolescents [ 54 56 ].…”
Section: Introductionmentioning
confidence: 99%